Hot Deformation Behavior and Processing Maps of Vapor-Phase-Grown Carbon Nanofiber Reinforced 7075Al Composites - Mengying Zhu; Zhefeng Xu; Junhua Wu; Satoshi Motozuka; Caili Tian; Jianglong Gu; Jinku Yu (Metals)
The present study prepared 7075Al composites reinforced with vapor-phase-grown carbon nanofibers (VGCNFs) using the spark plasma sintering (SPS) method. Constitutive equations of the composites were calculated, and thermal processing maps were constructed by performing thermal compression tests on the VGCNF/7075Al composites at deformation temperatures ranging from 300 to 450 °C and strain rates from 0.01 to 1 s−1. This study analyzed the microstructural evolution of the VGCNF/7075Al composites during the thermomechanical processing. The experimental results demonstrated that dynamic recrystallization (DRX) primarily governed the softening mechanism of VGCNF/7075Al composites during thermomechanical processing. At high strain rates, a combination of dynamic recovery (DRV) and DRX contributed to the softening behavior. The incorporation of VGCNFs results in higher dislocation density and a larger orientation deviation within the 7075Al matrix during the thermomechanical deformation process, providing stored energy that facilitated DRX. The activation energy for deformation of VGCNF/7075Al composites was 175.98 kJ/mol. The constitutive equation of the flow stress showed that a hyperbolic sinusoidal form could effectively describe the relationship between flow stress, strain, strain rate, and temperature of VGCNF/7075Al composites. The optimal thermomechanical deformation parameters for VGCNF/7075Al composites were 400–450 °C and 0.01–0.1 s−1 when the strain ranged from 0.05 to 0.15. For strains between 0.25 and 0.35, the optimal thermomechanical parameters were 380–430 °C and 0.01–1 s−1.